Advanced imaging of right ventricular anatomy and function. Issue 19 (3rd July 2020) - Badano, Luigi P; Addetia, Karima; Pontone, Gianluca; Torlasco, Camilla; Lang, Roberto M; Parati, Gianfranco; Muraru, Denisa
Abstract : Right ventricular (RV) size and function are important predictors of cardiovascular morbidity and mortality in patients with various conditions. However, non-invasive assessment of the RV is a challenging task due to its complex anatomy and location in the chest. Although conventional echocardiography is widely used, its limitations in RV assessment are well recognised. New techniques such as three-dimensional and speckle tracking echocardiography have overcome the limitations of conventional echocardiography allowing a comprehensive, quantitative assessment of RV geometry and function without geometric assumptions. Cardiac magnetic resonance (CMR) and CT provide accurate assessment of RV geometry and function, too. In addition, tissue characterisation imaging for myocardial scar and fat using CMR and CT provides important information regarding the RV that has clinical applications for diagnosis and prognosis in a broad range of cardiac conditions. Limitations also exist for these two advanced modalities including availability and patient suitability for CMR and need for contrast and radiation exposure for CT. Hybrid imaging, which is able to integrate anatomical information (usually obtained by CT or CMR) with physiological and molecular data (usually obtained with positron emission tomography), can provide optimal in vivo evaluation of Rv functional impairment. This review summarises the clinically useful applications of advanced echocardiography techniques, CMR and CT for comprehensive assessment of RV size, function and mechanics.